PENARIKAN BARANG YANG MENJADI OBYEK SEWA BELI DALAM HAL PEMBELI SEWA WANPRESTASI - Putu Sumiasi (University of Udayana, 2013)
The article entitled The Withdrawal of the Leasing Object in the event ofCustomer’s Default in Payment. The main issue discussed is that whether thewithdrawal of the leasing object is acceptable by the law in the event ofcustomer’s default in payment.The research in this paper is classified as a Normative Legal research, whichis based on primary and secondary legal materials. The approach taken was thestatutory and the analytical conceptual approach.The research results indicate that with the withdrawal of leasing object in alease agreement by the creditor according to law (under the provisions of Article 1338of Indonesian Civil Code) can be justified and lawful. The agreement of waivingthe provisions of article 1266 of paragraph 2 of Indonesian Civil Codebinding on the partie based on the principle of freedom of contract